The Expanding Therapeutic Perspective of CCR5 Blockade - Vangelista, Luca; Vento, Sandro (Frontiers in Immunology, 2018)
CCR5 and its interaction with chemokine ligands have been crucial for understanding and tackling HIV-1 entry into target cells. However, over time, CCR5 has witnessed an impressive transition from being considered rather unimportant in physiology and pathology to becoming central in a growing number of pathophysiological conditions. It now turns out that the massive efforts devoted to combat HIV-1 entry by interfering with CCR5, and the subsequent production of chemokine ligand variants, small chemical compounds and other molecular entities and strategies, may set the therapeutic standards for a wealth of different pathologies. Expressed on various cell types, CCR5 plays a vital role in the inflammatory response by directing cells to sites of inflammation. Aside HIV-1, CCR5 has been implicated in other infectious diseases and non-infectious diseases such as cancer, atherosclerosis and inflammatory bowel disease. Individuals carrying the CCR532 mutation live a normal life and are warranted a natural barrier to HIV-1 infection. Therefore, CCR5 antagonism and gene-edited knock out of the receptor gained growing interest for the therapeutic role CCR5 blockade may play in the attenuation of the severity or progression of numerous diseases.